Interleukin-17A Gene Variability in Patients with Type 1 Diabetes Mellitus and Chronic Periodontitis: Its Correlation with IL-17 Levels and the Occurrence of Periodontopathic Bacteria - Petra Borilova Linhartova; Jakub Kastovsky; Svetlana Lucanova; Jirina Bartova; Hana Poskerova; Jan Vokurka; Antonin Fassmann; Katerina Kankova; Lydie Izakovicova Holla (Hindawi Limited, 2016)
Interleukin-17 contributes to the pathogenesis of type 1 diabetes mellitus (T1DM) and chronic periodontitis (CP). We analyzed IL-17A −197A/G and IL-17F +7488C/T polymorphisms in T1DM and CP and determined their associations with IL-17 production and occurrence of periopathogens. Totally 154 controls, 125 T1DM, and 244 CP patients were genotyped using 5' nuclease TaqMan® assays. Bacterial colonization was investigated by a DNA-microarray kit. Production of IL-17 after in vitro stimulation of mononuclear cells by mitogens and bacteria was examined by the Luminex system. Although no differences in the allele/genotype frequencies between patients with CP and T1DM + CP were found, the IL-17A −197 A allele increased the risk of T1DM (P<0.05). Levels of HbA1c were significantly elevated in carriers of the A allele in T1DM patients (P<0.05). Production of IL-17 by mononuclear cells of CP patients (unstimulated/stimulated by Porphyromonas gingivalis) was associated with IL-17A A allele (P<0.05). IL-17A polymorphism increased the number of Tannerella forsythia and Treponema denticola in patients with CP and T1DM + CP, respectively (P<0.05). IL-17A gene variability may influence control of T1DM and the "red complex" bacteria occurrence in patients with CP and T1DM + CP. Our findings demonstrated the functional relevance of the IL-17A polymorphism with higher IL-17 secretion in individuals with A allele.